A curative‐intent endoscopic surgery for postradiation nasopharyngeal necrosis in patients with nasopharyngeal carcinoma. Issue 1 (22nd December 2018) - Zou, Xiong; Wang, Shun‐Lan; Liu, You‐Ping; Liu, Yan‐Ling; Zou, Ru‐Hai; Zhang, Yi‐Nuan; You, Rui; Yang, Qi; Xie, Yu‐Long; Lin, Mei; Huang, Pei‐Yu; Jiang, Rou; et al.
Abstract: Background: Postradiation nasopharyngeal necrosis (PRNN) is a severe complication after radiotherapy in patients with nasopharyngeal carcinoma (NPC), which can severely affect the quality of life and threaten the patient's life. Only 13.4%–28.6% of patients can be cured by traditional repeated endoscopic debridement. Here, we introduced an innovative curative‐intent endoscopic surgery for PRNN patients and evaluated its clinical efficacy. Methods: Clinical data of 72 PRNN patients who underwent radical endoscopic necrectomy, followed by reconstruction using a posterior pedicle nasal septum and floor mucoperiosteum flap were analyzed to determine the efficacy of this surgery. The endpoints were complete re‐epithelialization of the nasopharyngeal defect, relief of headache, and overall survival (OS). Results: All surgeries were successfully performed without any severe postoperative complications or death. The median value of numeric rating scales of pain decreased from 8 before surgery to 0 after surgery ( P < 0.001). Fifty‐one patients (70.8%) achieved complete re‐epithelialization of the nasopharyngeal defect. The number of cycles of radiotherapy (odds ratio [OR], 7.254; 95% confidence interval [CI] 1.035–50.821; P = 0.046), postoperative pathological result (OR, 34.087; 95% CI 3.168–366.746; P = 0.004), and survival status of flap (OR, 261.179; 95% CI 17.176–3971.599; P < 0.001) were independent risk factors of re‐epithelialization of the nasopharyngeal defects. Postoperative pathological result (hazard ratio [HR], 5.018; 95% CI 1.970–12.782; P = 0.001) was an independent prognostic factor for OS. The 2‐year OS rate of the entire cohort was 77.9%. Conclusion: Curative‐intent endoscopic necrectomy followed by construction using the posterior pedicle nasal septum and floor mucoperiosteum flap is a novel, safe, and effective treatment of PRNN in patients with NPC.